2019
DOI: 10.2147/cia.s211568
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cognitive functioning enhancement in older adults: is there an advantage of multicomponent training over Nordic walking?</p>

Abstract: IntroductionWe compared Nordic walking training (NW) to a multicomponent training (MCT) program of an equivalent intensity, in older adults. Our main hypothesis was that MCT would result in larger effects on cognitive processes than NW.MethodsThirty-nine healthy older adults, divided into two groups (NW and MCT), took part in the study (17 males, 22 females, mean age =70.8±0.8 years). They were tested for cardiovascular fitness, motor fitness and cognitive performance during the two weeks preceding and followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 35 publications
8
40
0
Order By: Relevance
“…Indeed, it has been previously demonstrated that coordination training specifically impacts visuospatial capacities [ 12 , 14 ]. With respect to physical fitness, reflected by cardiovascular capacities, in accordance with Temprado and colleagues’ [ 27 ] study, it is expected that all three groups will improve their cardiovascular capacities. This could occur if the mean level of effort, indexed by mean heart rate calculated during the different sessions for the three training programs, is roughly equivalent [ 27 ].…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Indeed, it has been previously demonstrated that coordination training specifically impacts visuospatial capacities [ 12 , 14 ]. With respect to physical fitness, reflected by cardiovascular capacities, in accordance with Temprado and colleagues’ [ 27 ] study, it is expected that all three groups will improve their cardiovascular capacities. This could occur if the mean level of effort, indexed by mean heart rate calculated during the different sessions for the three training programs, is roughly equivalent [ 27 ].…”
Section: Discussionsupporting
confidence: 66%
“…Walking sticks will be provided by the coach to participants. As in our previous study [ 27 ], the coach will progressively increase the level of difficulty over the 8 weeks, trying to individualize, as far as possible, the requested effort level while managing the whole group in the nature park. The participants will be following the coach, who shows the way and adapts the walking speed and difficulty.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations